2008
DOI: 10.1089/jpm.2007.0106
|View full text |Cite
|
Sign up to set email alerts
|

End-of-Life Care in Adults with Cystic Fibrosis

Abstract: We conclude that the circumstances surrounding the death of patients with CF holds challenges for their effective palliative care. CF patients continue life prolonging and preventative treatments until the last hours of life. There is an urgent need to examine palliative care approaches that may usefully coexist with maintaining transplantation options in the end-of-life care of this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 8 publications
1
35
0
Order By: Relevance
“…Hope is therefore maintained through periods of silence, allowing patients to circumvent information that may diminish hope. Whilst patients want to know more about end of life, few had actually initiated it [4,12]. The staff found themselves colluding with patients' positivity which hindered communication.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Hope is therefore maintained through periods of silence, allowing patients to circumvent information that may diminish hope. Whilst patients want to know more about end of life, few had actually initiated it [4,12]. The staff found themselves colluding with patients' positivity which hindered communication.…”
Section: Discussionmentioning
confidence: 99%
“…Those with non-malignant disease have been described, however, as the "disadvantaged dying" [3] as they frequently are not referred to palliative care services [4,5] and may benefit from better resourced palliative care. There has been limited attention exploring the palliative care and psychosocial needs of adults with non-malignant disease facing end of life.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Integration of a palliative care approach with hematopoietic stem cell or solid organ transplantation has been recently proposed. [40][41][42] Song et al have found that barriers to integrating palliative care with lung transplantation include providers' misconceptions that palliative care is equivalent to EOL care, difficulty in discussing palliative care with families, and uncertainty about prognosis. 43 Pediatricians and nurses report similar barriers to the provision of pediatric palliative care in ICU and non-ICU settings, including prognostic uncertainty.…”
Section: Discussionmentioning
confidence: 99%